Recurrent stroke in varicella zoster associated vasculopathy - Maurya, Pradeep Kumar; Singh, Ajai Kumar; Tiwari, Ashutosh; Qavi, Abdul (Nepal Journal of Neuroscience, 2021)
Varicella zoster virus (VZV) is well known for its neurotropism, primary infection and reactivation after variable latency periods. After reactivation from spinal or cranial nerve ganglia, viruses can affect the central nervous system and cranial vasculature via transaxonal migration followed by transmural spread from the adventitial layer to the intima. Stroke can occur following primary infection by VZV (varicella) or after reactivation (zoster). These infectious vasculitides by VZV can lead to unifocal or multifocal ischemic and hemorrhagic stroke either after cranial nerve or spinal dermatomal zoster. Usual difference between immunocompetent versus immunocompromised individuals is involvement of unifocal large vessel vasculopathy in the former while multifocal small vessel in later. This vasculopathy in some cases may be progressive leading to recurrent stroke even after antiviral treatment. Diagnosis becomes challenging and needs a high degree of suspicion in immunocompetent, younger individuals, in absence of rash and when there are comorbidities. We report a case of elderly immunocompetent women, who developed multifocal infarcts followed by ventricular and subarachnoid haemorrhage after thoracic varicella zoster. Diagnosis was confirmed by the presence of anti-VZV IgG antibodies in the cerebrospinal fluid. In view of the diverse clinic-radiological spectrum of VZV vasculopathy, early recognition of this clinical entity is warranted for improved outcome.